Perdagangan Luar Negeri Indonesia-Amerika Serikat - Darman Darman (Binus Business Review, 2013)
This study aims to identify and analyze: how international trade relations are between Indonesia and the United States, especially in the export-import of goods, particularly non-oil exports; how the value is obtained from the export-import of goods between Indonesia-United States, whether Indonesian exports to the United States greater than Indonesian import from the United States; who gets the surplus of trade between the two countries; and how big the export-import growth rate is, whether Indonesia tends to become exporter or importer. Data used in this study were a time series of the year 2008-2012. The analytical method used was the growth formula and Trade Specialization Index. Based on the trade balance, the value of Indonesian exports, both oil and non-oil, the United States has a surplus and vice versa. In other words, the United States includes a country of Indonesia's main export, in addition to Japan and China. Value of Trade Specialization Index for both oil and non-oil exports is positive above 0 to 1, then the oil and non-oil commodities have strong competitiveness. Indonesia is likely as a means exporter of the commodity. However, based on 10 major Indonesian export commodities to the United States, as the largest foreign exchange earner for textile examples and textile products, footwear industries, electronic products, furniture, as well as horticultural commodities, is threatened lethargic, because shutdown policy decisions on the government services were feared to reduce consumption of the American people’s imported products.